(untitled) (CIPEEX, 2022)
The process of deafness occurs with the structural damage of the outer/middle ear, which functions to carry sound to the inner ear, and can be conductive, sensorineural, mixed, or central. The most common type of hearing loss can be temporary or permanent1. One of the ways deaf people communicate is through Brazilian Sign Language (LIBRAS)2, which uses the visual, cognitive, and upper limb systems to produce words. The electroencephalogram is used in the deaf3 population as a model of neurodynamic assessment with results in multi-scale neuro-physical that maps the late brain responses to the effort exerted4. It is known that there is movement of the upper limbs (ULs) such as the shoulder, arm, elbow, forearm, wrist, hands, and fingers in the process of translating and interpreting signs. Given this, there is information being transmitted directly by the brain during interpretation. However, there are no studies that correlate the evaluations, which justifies the objective of the present study, which is to evaluate fluency, cerebral electrical activity, and upper limb movement during the execution of the universal sign - Jesus - in Brazilian Sign Language.